Mobbing jako problem etyki w zarządzaniu - Kowal, Jolanta; Pilarek, Grażyna (Annales. Etyka w Życiu Gospodarczym, 2011)
The positive company image and its good reputation are usually results of ethical and honest behaviour towards employees and may cause competitiveness and benefits increase, customer satisfaction and new job places creating. However it occurs often in dynamically developing firms that ethical norms are not kept and this process is observed by lack of equal chances to get a job – people without connections remain without work. Due to different research the very serious problem is a phenomena of mobbing. Psychological terror or mobbing in working life involves hostile and unethical communication which is directed in a systematic manner by one or more individuals, mainly toward one individual, who, due to mobbing, is pushed into a helpless and defenceless position and held there by means of continuing mobbing activities. These actions occur on a very frequent basis (statistical definition: at least once a week) and over a long period of time (statistical definition: at least six months´ duration). Because of the high frequency and long duration of hostile behaviour, this maltreatment results in considerable mental, psychosomatic and social misery.